Measurement of 3 Solar Panel Output with Different Treatment Involving Controller and Reflector - Yulinar Adnan; Khairul Saleh; Assaidah Assaidah (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
Solar cell as one of renewable energy source had been treated differently in this research. In order to optimize its output and efficiency, three panels output was measured simultaneously by vary its movement and sun light exposure. The variations of measurement  are one static panel without any treatment; one static panel with two mirrors as reflector; and one dynamic panel with reflector. The dynamic panel movement controlled by microcontroller. Result had revealed that the treatment succesfully improve the output of solar cell.